2016
DOI: 10.1186/s12936-016-1468-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomic analyses of Enterobacter, Anopheles and Plasmodium reciprocal interactions that impact vector competence

Abstract: BackgroundMalaria exerts a tremendous socioeconomic impact worldwide despite current control efforts, and novel disease transmission-blocking strategies are urgently needed. The Enterobacter bacterium Esp_Z, which is naturally harboured in the mosquito midgut, can inhibit the development of Plasmodium parasites prior to their invasion of the midgut epithelium through a mechanism that involves oxidative stress. Here, a multifaceted approach is used to study the tripartite interactions between the mosquito, Esp_… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 72 publications
3
50
0
Order By: Relevance
“…Host pathways and processes known to influence microbiota in mosquitoes include immunity, amino acid metabolism, reactive oxygen species, and calcium transport ( Kumar et al, 2010 ; Stathopoulos et al, 2014 ; Pang et al, 2016 ; Short et al, 2017 ; Xiao et al, 2017 ; Zhao et al, 2017 ). Additionally, serial passaging of gut symbionts in mosquitoes selected for isolates that persist in the gut for longer periods of time ( Riehle et al, 2007 ; Dennison et al, 2016 ), indicating that bacterial genetics is also important in shaping the microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…Host pathways and processes known to influence microbiota in mosquitoes include immunity, amino acid metabolism, reactive oxygen species, and calcium transport ( Kumar et al, 2010 ; Stathopoulos et al, 2014 ; Pang et al, 2016 ; Short et al, 2017 ; Xiao et al, 2017 ; Zhao et al, 2017 ). Additionally, serial passaging of gut symbionts in mosquitoes selected for isolates that persist in the gut for longer periods of time ( Riehle et al, 2007 ; Dennison et al, 2016 ), indicating that bacterial genetics is also important in shaping the microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…Another stably inherited gut commensal bacteria, Asaia, can be genetically modified and directly inhibits pathogen development by secreting antiplasmodial effectors [23]. In addition, these microbes inhibit parasites indirectly through promoting the formation of PM and stimulating the oxidative defense system and NF-κB dependent immune responses [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that certain species of bacteria can inhibit Plasmodium development [2][3][4]. For example, Enterobacter bacteria that reside in the Anopheles midgut can inhibit the development of Plasmodium parasites prior to their invasion of the midgut epithelium [5,6].Wolbachia endosymbiotic bacteria are estimated to naturally infect ~40% of insect species [7] including mosquito vector species that are responsible for transmission of human diseases such as Culex (Cx.) quinquefasciatus [8][9][10] and Aedes (Ae.)…”
mentioning
confidence: 99%
“…Numerous studies have shown that certain species of bacteria can inhibit Plasmodium development [2][3][4]. For example, Enterobacter bacteria that reside in the Anopheles midgut can inhibit the development of Plasmodium parasites prior to their invasion of the midgut epithelium [5,6].…”
mentioning
confidence: 99%